DRY EYE SYNDROME: PROBLEMS OF DIAGNOSIS AND TREATMENT - Светлана Ивановна Елгина; Евгения Алексеевна Созуракова; Елена Владимировна Рудаева; Наталья Степановна Черных; Кира Борисовна Мозес; Яэль Центер; Елизавета Евгеньевна Паньшина; Елизавета Дмитриевна Егорова; Алена Ивановна Пахолкина; Сона Ханларовна Мазанова (Медицина в Кузбассе, 2024)
Dry eye syndrome (DES) is widespread throughout the world's population. In recent years, a large number of research papers have been devoted to the causes, methods of diagnosis and treatment of this problem. The factors that a person directly encounters in everyday life and in the course of his professional activities have been studied. To date, the influence of visual stress, the amount of screen time, working with digital and paper media, taking certain groups of medications, gender and age has been proven. It has been established that every year the proportion of ophthalmological patients who are diagnosed with dry eye syndrome for the first time is increasing. A significant disadvantage is that currently the detection of dry eye syndrome is carried out at late stages. This happens for a number of reasons: patients notice symptoms of dry eye syndrome in the later stages, and, accordingly, seek specialized help in advanced conditions; Ophthalmologists often regard the signs of dry eye syndrome as a symptom of another disease, and not an independent disease, and, therefore, do not carry out diagnostic and therapeutic measures. Also, modern research works do not emphasize the importance of an individual approach to individual clinical cases. The importance of studying this problem from this aspect is obvious, since it is necessary to take into account existing risk factors as a possible cause of dry eye syndrome, which affect a particular patient in order to select effective therapeutic tactics